Application of UV/TiO2 advanced oxidation in treating oily compost leachate generated during oily sludge composting - Tajik, Reza; Godini, Kazem; Saeedini, Reza; Mashayekhi, Masoumeh; Koolivand, Ali (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this work, oily compost leachate (OCL) generated during oily sludge composting was treated by UV/TiO2. OCL subsamples, gathered bi-weekly from the composting process, were thoroughly mixed and then filtered to reduce the solution turbidity. The effects of initial chemical oxygen demand (COD) concentration, UV type (A and C), pH (3, 7, and 11), reaction time (30, 60, 90, and 120 min), and TiO2 concentration (0.5, 1, and 2 g L-1) on the total petroleum hydrocarbons (TPH) and COD removal from OLC were examined.
Keywords: petroleum; oily sludge; oily sludge composting; leachate treating; oxidation; ropa naftowa; szlamy; kompostowanie osadów olejowych; oczyszczanie odcieków; utlenianie